Language regression is associated with faster early motor development in children with autism spectrum disorder. Issue 1 (30th August 2019) - Manelis, Liora; Meiri, Gal; Ilan, Michal; Flusser, Hagit; Michaelovski, Analya; Faroy, Michal; Kerub, Orly; Dinstein, Ilan; Menashe, Idan
Abstract : Language regression (LR) is a consistent and reproducible phenomenon that is reported by 25% of parents who have children with autism spectrum disorder (ASD). However, there is controversy regarding the etiological and clinical significance of this phenomenon. Here, we examined data from a cohort of 218 children with ASD from the Negev Autism Center in Israel. We identified 36 children with ASD who were reported to exhibit clear LR by their parent on three independent occasions and compared them to 104 children whose parents did not report any concern of regression (NR). We compared a variety of key developmental characteristics across these two groups. We found that the age at which children with ASD in the LR group achieve key developmental milestones of crawling, walking, and use of first words is significantly younger than the age of children in the NR group, and comparable to the age of typically developing children. In contrast, no differences were observed in physical growth characteristics such as head circumference, weight, or height between the groups. Furthermore, almost all children with LR were born close to full term (>35 weeks) and none had a history of hypotonia. Notably, despite their apparently typical early development, children with LR were diagnosed with more severe symptoms of ASD than children with NR. These results strengthen the motivation to continue and study LR among children with ASD and suggest that early detection and intervention studies of ASD may benefit from stratifying children into LR and NR groups. Autism Res 2020, 13: 145–156 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The presence of language regression (LR) among children with autism is still a matter of scientific debate. Here, we show that children with autism and reported LR start to crawl, talk, and walk at the same age as other typically developing children and significantly earlier than other children with autism. These findings, along with other medical differences between these groups, suggest that children who experienced LR comprise a distinct subgroup within the autism spectrum.